Identity in Adolescents Born From Genocidal Rape. Issue 3 (2nd July 2016) - Kamuzinzi, Masengesho
ABSTRACT: This research was inspired by an observation that some adolescents born from genocidal rapes became identity achievers, despite the fact that they did not benefit from significant support from family and community members. This article investigates factors orienting such adolescents toward a mature, foreclosed, or a diffused status. As existing research did not sufficiently explore identity formation in such atypical circumstances, a new analysis model is proposed. Field investigations were conducted in the form of an in-depth case study involving 20 adolescents born from genocidal rape. Key findings show that identity assumed through identity formation processes emerges as a negotiated outcome of the confrontation of subjective and attributed identities. Four scenarios emerging from this confrontation are explored and illustrated.